HUBUNGAN BOBOT LAHIR ANAK BABI DENGAN PERTAMBAHAN BOBOT BADAN, BOBOT SAPIH, MORTALITAS, DAN LITTER SIZE SAPIHAN PADA PETERNAKAN PT. KARYA PROSPEK SATWA - Bunok, Debora K.I.; Lapian, M.Th.R.; Rawung, V.R.W.; Rembet, G.D.G. (ZOOTEC, 2020)
RELATIONSHIP OF WEIGHT BIRTH PIGLET WITH ADDITION OF AGENCY WEIGHT, WEANING WEIGHT, MORTALITY, AND LITTER SIZE WEANING IN LIVESTOCK PT. KARYA PROSPEK SATWA. This study aims to determine how much the relationship of birth weight with weight gain, weaning weight, mortality, and litter size of weaning in animal husbandry companies owned by Animal Prospects. The material used is 7 pregnant sows from Yorkshire and Landrace, with an average body weight of 140 kg which will be taken by 54 children randomly. Furthermore, this research data obtained from weighing piglets during parturition, weighing weekly during weaning and weighing when weaned and taking data on live and dead piglets during the study. The data is then processed by procentage descriptive method and evaluated by simple correlation (r) and determination (R) tests. The variables measured in the study were body weight gain, weaning weight, mortality, and weaning litter size. Birth weight has a very close relationship with weight gain and weaning weight, but litter size weaning has a very weak relation. While mortality is not related.Â Key words: Piglets, Birth weight, Weight gain, Weaning weight, Mortality, Litter size weaning.